From classrooms to Screens: The evolution of Science education in the pandemic era (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
The COVID -19 pandemic disrupted traditional education systems worldwide. Science education especially teaching Physics during the pandemic era without face-to-face contact with students in the classrooms was quite a tough job; of course, it was the challenge put by natural calamity hence it was an unavoidable situation; even though preparing colorful images and making PowerPoint presentation that calamity was overcome and proper teaching was being done but one of the problems was that those students who were unable to join lectures as per time table due to technical problem I was recording lectures and was preparing videos with OBS( Open Broadcaster Software) and I was uploading all the recorded lectures students those were not attending lectures were attending at any time anywhere. Apart from college students worldwide, it was beneficial for mankind. Proper colorful figures and appropriate presentation make it easy for students to understand the Physics subject. In the present paper, I am mentioning that Koening’s method experiment and topic related to elasticity and optics were being viewed by most of the viewers. All videos related to the articles/experiments were uploaded on a YouTube channel titled “Turbulent Tech World”